ANALYSIS OF PT MEST INDONESIY'S MARKETING STRATEGY IN ORDER TO INCREASE TRUST AND FERTILIZER SALES - KASMAD; MADDINSYAH, ALI; ROMMY PRAMUDIA MULYA SIDAURUK; VIKA OKTAVIANI, (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT – Each The objectives of this research are 1) to describe and analyze PT's marketing strategy. Mest Indonesiy in order to increase trust and fertilizer sales. 2) To describe and analyze the obstacles to PT's marketing strategy. Mest Indonesiy in order to increase trust and fertilizer sales. 3) To describe and analyze solutions to PT's marketing strategy obstacles. Mest Indonesiy in order to increase trust and fertilizer sales. This type of research is a qualitative approach using descriptive methods. The population in this study were 5 informants at PT. Mest Indonesiy. The sampling technique uses a purposive technique, the samples are the Managing Director, Marketing Director, Marketing Manager and two consumers. Data collection techniques use Focus Group Discussion, Interview, Observation, Documentation Method. The data analysis technique used is SWOT analysis. The results of this research show that 1) PT. Fertilizer marketing strategy. Mest Indonesiy emphasizes the superior quality of its products, encouraging continuous research and development. Product prices are considered taking into account market analysis and competitive factors to provide appropriate value to customers. Collaboration with agricultural institutions, universities and research institutions can increase customer confidence through workshops and seminars. The packaging design reflects the quality and value of the product. 2) PT. Mest Indonesiy faces obstacles in increasing trust and sales of fertilizer, including difficult access to the product, limited stock, and a lack of information about use and dosage. Consumers have difficulty finding products in local farm stores, often have competition, and experience inconvenience in the purchasing process. 3) Solutions to overcome obstacles involve increasing fertilizer formulation innovation, closer collaboration for distribution, and adjusting promotional strategies. Supply chain transparency, optimizing online shipping, and diversifying warehouse locations are important strategies to overcome logistics constraints. Efficient financial management, focus on local markets or diversification, and competitive pricing are solutions to face external challenges. Implementation of this strategy is expected to strengthen PT's position. Mest Indonesiy in the market, build customer trust, and increase sales of fertilizer products.